Avian fossil assemblages at the onset of the LGM in the Eastern Alps: a palaecological contribution from the Rio Secco Cave (Italy) - Carrera, Lisa; Pavia, Marco; Romandini, Matteo; Peresani, Marco (Comptes Rendus Palevol, 2018)
The avian fossil assemblages from the late Pleistocene deposits of the Rio Secco Cave (north-eastern Italy) is presented herein. We studied the layers that date back to the end of MIS3 and the beginning of MIS2, which also contain evidence of Gravettian frequentation dated to 33.5–30 ka cal BP. The systematic analysis revealed the presence of 18 species and other supraspecific taxa that supported palaeoenvironmental reconstructions. Taxa indicate that, at the onset of LGM, site surroundings were characterised by conifer or mixed forests, open grasslands, slow-flowing water bodies and mountain meadows with rocky outcrops, as indicated by Lagopus muta. Today, this environment is found above the tree line (beyond 1500–2000 m) and cannot be detected near the site, located at 580 m asl. Noteworthy, is also the finding of the second Italian late Pleistocene fossil record of Picus canus.